1984
DOI: 10.2337/diacare.7.5.465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Ingestion on the Glucose and Insulin Response to a Standardized Oral Glucose Load

Abstract: Type II diabetic subjects were given 50 g protein, 50 g glucose, or 50 g glucose with 50 g protein as a single meal in random sequence. The plasma glucose and insulin response was determined over the subsequent 5 h. The plasma glucose area above the baseline following a glucose meal was reduced 34% when protein was given with the glucose. When protein was given alone, the glucose concentration remained stable for 2 h and then declined. The insulin area following glucose was only modestly greater than with a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
214
7
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(240 citation statements)
references
References 22 publications
16
214
7
3
Order By: Relevance
“…A smaller difference in protein intake was seen between the CHO and MUFA diets (Table 1), attaining 10 g protein per day. In Type-2 DM subjects only larger amounts of protein ( b 30 g) would in¯uence glucose or insulin responses (Nuttall et al, 1984;Rasmussen et al, 1990). In our study no difference in either glucose or insulin levels were seen, for which reason it seems unlikely that the observed difference in protein ingestion in¯uenced the results in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…A smaller difference in protein intake was seen between the CHO and MUFA diets (Table 1), attaining 10 g protein per day. In Type-2 DM subjects only larger amounts of protein ( b 30 g) would in¯uence glucose or insulin responses (Nuttall et al, 1984;Rasmussen et al, 1990). In our study no difference in either glucose or insulin levels were seen, for which reason it seems unlikely that the observed difference in protein ingestion in¯uenced the results in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Factors affecting the rate of glucose absorption from starchy food and therefore the GI value include (1) the nature of the food and (2) the type and extent of food processing (Table 5). The former includes the ratio of amylose to amylopectin present in the raw food (Behall et al, 1988) and the type of monosaccharide components, the amount and type of dietary fiber (Jenkins et al, 1978), the presence of large amounts of fat or protein (Nuttall et al, 1984;Wolever et al, 1985;Collier et al, 1986;Bornet et al, 1987), antinutrients such as phytic acid, lectins and tannins (Yoon et al, 1983;Thompson et al, 1984;Rea et al, 1985) and nutrient -starch interactions in carbohydrate-containing foods, such as in wheat products (Jenkins et al, 1987a). Extrusion, flaking, grinding, canning, storing and cooking of the carbohydrate-containing foods can affect the particle size and the integrity of the starch granules (Jenkins et al, 1988a) and plant cell walls (Ellis et al, 1991), making the carbohydrate portion more accessible to digestive enzymes (Wolever, 1990;Collins et al, 1981).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Fat and protein may modify the glycemic response to a carbohydrate food by slowing gastric emptying (Welch et al, 1987) and increasing insulin secretion, respectively (Nuttall et al, 1984;Gannon et al, 1988). However, it has been shown that neither fat nor protein in the amounts found in most foods (with the exception of peanuts and most nuts) Lower postprandial glucose rise (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Reduced daily mean insulin levels (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993;Jones et al, 1993) Flatter gastric inhibitory polypeptide response (Jenkins et al, 1990(Jenkins et al, ,1992Bertelsen et al, 1993) Decreased 24 h urinary C-peptide output (Jenkins et al, 1989(Jenkins et al, ,1992 Prolonged suppression of plasma free fatty acids (Jenkins et al, 1990) Reduced urinary catecholamine output (Jenkins et al, 1990) Lower total and LDL cholesterol levels (Jenkins et al, 1989Arnold et al, 1993;Cohn 1964) Reduced hepatic cholesterol synthesis (Jones et al, 1993) Decreased serum apolipoprotein B levels (Jenkins et al, 1989) Decreased serum uric acid levels Raised urinary uric acid excretion Adapted from Jenkins et al (1995).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Previous research has demonstrated that co-ingestion of proteins with carbohydrates results in increased plasma insulin responses (Rabinowitz et al, 1966;Pallotta and Kennedy, 1968), both in healthy subjects (van Loon et al, 2000;Calbet and MacLean, 2002) and in patients with type II diabetes (Nuttall et al, 1984;Manders et al, 2005Manders et al, , 2006. The effect of proteins on insulin secretion is mainly a consequence of the effect that specific amino acids in the blood have on pancreatic b-cell activity (Newsholme et al, 2005).…”
Section: Introductionmentioning
confidence: 99%